HAKIKAT MANUSIA DALAM KAJIAN NASKAH MAKRIFATULLAH KARYA HAJI SULAIMAN TARIF BIN TARIF - Ridwan, Ridwan (Jurnal Ilmu Budaya, 2016)
Manuscript "Ma'rifatullah" is a manuscript written in Malay, written by Haji Sulaiman Tarip bin Haji Tarip, and rewritten by anonymous writer on Ramadhan 30, 1409 H/May 9th, 1979. Jhis manuscript has been analyzed with dtferent focuses. The first analysis is a trunsliteration from Malay to Latin and the later analysis focuses on the essence of human being found in the manuscript.